LDLc reduction with fixed-dose combination rosuvastatin-ezetimibe in patients with coronary heart disease that are not candidates for PCSK9 inhibitors treatment. (14th October 2021) - Cordero, A; Escribano, D; Bertomeu-Gonzalez, V; Lopez-Ayala, J M; Monteagudo, M; Quintanilla, A M; Moreno-Arribas, J; Perez-Berbell, P; Zuazola, P
Abstract: Background: Statin plus ezetimibe combination has a recommendation class IIa, level of evidence B, for low-density lipoprotein cholesterol (LDLc) reduction. Since LDLc treatment target for patients with coronary heart disease (CHD) has been recently reduced to <55 mg/dl most patients might need lipid-lowering drugs combinations and fixed-dose combinations are known to increase adherence. Current indications for PCSK9 inhibitors accepted for reimbursement in Spain in patients with CHD are LDL >100 mg/dl despite maximal dose tolerated of statins or any of previous patients with statin intolerance and LDL >100 mg/dl. Methods: Investigator-initiated retrospective analysis of patients with coronary heart disease that received fixed-dose combination with rosuvastatin-ezetimibe between 2019 and 2020 in a specialized unit for patients with CHD. Inclusion criteria were: CHD and LDLc <100 mg/dl despite statin treatment or >100 mg/dl without previous lipid-lowering treatments. We also analysed patients in whom treatment was initiated at discharge from and acute coronary syndrome (ACS) or with chronic coronary syndrome (CCS) Results: We analyzed 137 patients, 79.4% males, mean age 62. (12.3) and 24.1% with ACS. Statin treatment before initiation fixed-dose combination was higher in patients with CCS (71.2% vs. 8.2%; p<0.01). Mean LDLc before treatment was 103.0 (30.5) mg/dl and it was higher in patients with ACS (121.3 (40.2) vs. 97.4 (24.4); p<0.001). Median time to second blood test was 203 days (IQR 122–300); mean post-treatment LDLc was 60.8 (21.2) mg/dl and no difference (p=0.18) was found in patients with ACS vs CCS: 56.0 (26.1) vs. 62.4 (19.2) mg/dl. Mean LDLc reduction was 38.5% and it was higher in was higher in ACS patients (49.9% vs. 34.7%) (figure). LDLc <55 mg/dl was achieved in 42.1% of the patients, more frequently in patients with ACS: 59.3% vs. 36.3% (p=0.036). No increase in transaminases was detected and a reduction in triglycerides was found (149.1 (100.4) to 124.7 (82.3) mg/dl; p=0.041). Conclusions: Treatment with a fixed-dose combination with rosuvastatin-ezetimibe in patients with CHD not candidate for PCSK9 inhibitors is effective and safe for LDLc reduction especially in patients discharged after an ACS. FUNDunding Acknowledgement: Type of funding sources: None.